Outbreak of pneumococcal pneumonia among shipyard workers in Marseille, France, January to February 2020 - Cassir, Nadim (Euro Surveill, 2020)
We report the third outbreak of pneumococcal pneumonia within one year among workers in European shipyards. During January and February 2020, 37 cases of pneumonia were identified in a shipyard in Marseille, south-eastern France. Outbreak control measures were implemented, including a mass vaccination campaign with 23-valent pneumococcal polysaccharide vaccine targeting all shipyard workers. Given the high mobility of shipyard workers, coordinated responses between European public health institutes are necessary to avoid further outbreaks.